Detection of wound healing disorders after major amputations by measurements of the microcirculation: A prospective single-center study - Zetzmann, Katharina; Papatheodorou, Nikolaos; Rühl, Eva; Yagshyyev, Shatlyk; Haney, Briain; Moosmann, Oxana; Li, Yi; Meyer, Alexander; Knieling, Ferdinand; Behrendt, Christian Alexander; Lang, Werner; Rother, Ulrich (SAGE Open Medicine, 2024)
Introduction: Although major amputations can often be avoided due to evolving methods of endovascular and surgical revascularizations techniques, in patients with chronic limb-threatening ischemia, it is still necessary in some cases. Aim of this study was the detection of wound healing disorders through intraoperative microcirculation measurements in major limb amputations. Materials and methods: In this single-center clinical study, patients with an indication for major amputation were enrolled prospectively. Cause of amputation, patients’ comorbidities including cardiovascular risk profile were assessed. Macrocirculation, as well as microcirculation were assessed. Microcirculation measurements were performed by fluorescence angiography with the administration of indocyanine green. A preoperative measurement was obtained at the amputation level, followed by three additional measurements of the amputation stump postoperatively. Wound healing was monitored and correlated with the microcirculatory findings, based on the perfusion parameters ingress and ingress rate, calculated in the indocyanine green fluorescence video sequences of the amputation stumps. Results: Forty-five patients were enrolled, including 19 (42%) below-the-knee amputations and 26 (58%) above-the-knee amputations. When considering the need for revision, a change in the microperfusion parameters was observed postoperatively. The mean value for ingress was significantly lower directly postoperatively in stumps requiring revisions (5 ± 0 A.U. versus 40.5 ± 42.5 A.U., p < 0.001). The mean value of ingress rate behaved similarly (0.15 ± 0.07 A.U./s versus 2.8 ± 5.0 A.U./s, p = 0.005). The evaluation of indocyanine green measurements when wound healing disorders occurred also showed nonsignificant differences in the mean values. Conclusion: Fluorescence angiography after major lower limb amputations appears to be an option of depicting microperfusion. Especially, the early postoperative detection of reduced perfusion can indicate a subsequent need for revision. Therefore, this method could possibly serve as a tool for intraoperative quality control after major limb amputation.
CRIS-Team Scopus Importer:2024-08-02
Keywords: fluorescence angiography; indocyanine green; Major limb amputation; microperfusion; wound healing

Independent Factors Influencing Changes in Baroreceptor Sensitivity after Carotid Endarterectomy - Yagshyyev, Shatlyk; Haney, Briain; Li, Yi; Papatheodorou, Nikolaos; Zetzmann, Katharina; Meyer, Alexander; Meyer, Sebastian; Lang, Werner; Rother, Ulrich (Annals of Vascular Surgery, 2024)
Background: Carotid endarterectomy (CEA) is a well-established standard therapy for patients with symptomatic or asymptomatic high-grade carotid stenosis. The aim of carotid endarterectomy is to decrease the risk of stroke and avoid relevant functional loss. However, carotid endarterectomy is known to be associated with hemodynamic dysregulation. In this study we compared eversion CEA (E-CEA) and conventional CEA (C-CEA) regarding postoperative blood pressure values as well as preoperative and postoperative baroreceptor sensitivity in the first 7 days after surgery. The aim was to find possible factors influencing changes in baroreceptor sensitivity. Methods: Patients (111 patients were enrolled, of which 50 patients received C-CEA and 61 patients E-CEA) were prospectively enrolled in this study. For the measurement of baroreceptor sensitivity, a noninvasive Finometer measuring device from Finapres Medical System B.V. (Amsterdam, The Netherlands) was used. Measurements were performed 1 day before surgery (PRE), directly after surgery (F1), on day 1 (F2), day 2 (F3), and on day 7 (F4) postoperatively. Results: Postoperative blood pressure values were significantly higher in the E-CEA group on the day of surgery (F1) (P < 0.001) and on day 1 (F2) (P < 0.001). From day 2 (F3, F4) postoperatively, no significant difference was found between the 2 groups. The invasive blood pressure measurement in the postoperative recovery room showed significantly higher systolic blood pressure values in the E-CEA group (P = 0.001). The need of acute antihypertensive therapy was significantly higher in the recovery room in the E-CEA group (P = 0.020). With regard to changes in baroreceptor sensitivity, significantly lower baroreceptor sensitivity (BRS) values were recorded in the E-CEA group at 1 day (F2) postoperatively (P = 0.005). The regression analysis showed that the applied surgical technique and the patient's age were significant factors influencing changes in baroreceptor sensitivity. Conclusions: In this study we could confirm higher blood pressure levels after E-CEA in the first 2 days after surgery. Additionally, we identified 22 factors possibly influencing baroreceptor sensitivity: surgical technique and age. Based on the data obtained in this study, hemodynamic dysregulation after CEA (E-CEA, C-CEA) is temporary and short-term. Already after the second postoperative day, there was no significant difference between the E-CEA and E-CEA groups, this effect remained stable after 7 days.
CRIS-Team Scopus Importer:2024-08-09

Intermittent negative pressure therapy in patients with no-option chronic limb-threatening ischemia - Yagshyyev, Shatlyk; Hausmann, Philipp; Li, Yi; Kempf, Julius; Zetzmann, Katharina; Dessi, Katia; Moosmann, Oxana; Almási-Sperling, Veronika; Meyer, Alexander; Gerken, Andreas L.H.; Lang, Werner; Rother, Ulrich (Vasa-Journal of Vascular Diseases, 2023)
Background: Aim of this study was to assess the influence of intermitted negative pressure (INP) therapy on the foot microcirculation in patients with no-option CLTI. Patients and methods: CLTI patients defined as no option for revascularization on the basis of an interdisciplinary vascular board decision (interventional radiology, vascular surgery) were included in this study. INP therapy was performed at home. Therapy regime was: 1 hour twice daily. Follow-up was after 6 weeks and 3 months. Microcirculation measurement was performed by laser Doppler flowmetry and white light spectrometry (oxygen to see, O2CTM). Following parameters were evaluated: oxygen saturation (sO2 in%), relative hemoglobin (rHb) and flow (in arbitrary units A.U.). Additionally the clinical outcome of the patients was assessed. Results: From September 2020 to June 2022, 228 patients were screened. In total 19 patients (13 men, 6 women, mean age was 73.95 years) were included. 6 weeks after INP therapy the microcirculation showed a significant improvement for the parameter sO2 (%) (p=0.004). After 3 months a non-significant decrease compared to 6 weeks follow-up was seen for the parameter sO2; however, the perfusion was still improved compared to baseline measurement. With regard to the microperfusion values flow (AU) and hemoglobin (AU), the changes were not significant. Clinically, the patients reported a significant reduction of rest pain after therapy (p=0.005). Conclusions: INP therapy in no-option CLTI patients showed a significant improvement of the skin perfusion after 6 weeks. Therefore, INP therapy might have therapeutic potential in these critical ill patients.
CRIS-Team Scopus Importer:2023-11-17
Keywords: chronic limb-threating ischemia; FlowOx; intermittent negative pressure; microperfusion; no-option patients; oxygen to see (O2C)

Long-Term Outcomes of Extra-Anatomic Femoro-Tibial Bypass Reconstructions in Chronic Limb-Threating Ischemia - Meyer, Alexander; Boxberger, Evgenia; Behrendt, Christian Alexander; Yagshyyev, Shatlyk; Welk, Irina; Lang, Werner; Rother, Ulrich (Journal of Clinical Medicine, 2022)
(1) Background: While tibial bypass surgery still plays a role in the treatment of patients with chronic limb-threatening ischemia and diabetic foot syndrome; only a few centers have recorded considerable numbers of these conditions. The current study aimed to determine contemporary practice with special focus on the performance of extra-anatomic grafting to the infrapopliteal arteries. (2) Methods: A retrospective, single-center study included patients with tibial bypass grafts from 1 January 2008 to 31 December 2019. Primary endpoints were complication rate, graft patency, amputation, overall survival, and major adverse cardiac (MACE) or limb event (MALE). The cohort was stratified by extra-anatomic vs. anatomic position. (3) Results: A total of 455 patients (31% female) with Rutherford stage 4 (12.5%) and 5/6 (69.5%) were included (thereof, 19.5% had high amputation risk according to the Wound Ischemia Foot Infection score). Autologous reconstruction was performed in 316 cases, and prosthetic reconstruction in 131 cases, with a total of 51 (11.2%) extra-anatomic grafts. Early occlusion rate was 9.0% with an in-hospital overall mortality of 2.8%. The in-hospital rate of MACE was 2.4% and of MALE, 1.5%. After one, three and five years, the primary patency of venous bypasses was 74.5%, 68.6% and 61.7%, respectively. For prosthetic grafts, this was 55.1%, 46.0%, and 38.3%, respectively (p < 0.001). The patency of extra-anatomic prosthetic grafts performed significantly better compared with anatomically positioned prosthetic grafts (log-rank p = 0.008). In multivariate analyses, diabetes (hazard ratio, HR 1.314, CI 1.023–1.688, p = 0.032), coronary artery disease (HR 1.343, CI 1.041–1.732, p = 0.023), and dialysis dependency (HR 2.678, CI 1.687–4.250, p < 0.001) were associated with lower odds of survival (4) Conclusion: In this large, single-center cohort, tibial bypass surgery demonstrated satisfactory results with overall low perioperative complication rates and long-term patency rates of 60% and 38%, respectively. Extra-anatomic bypasses represent a feasible alternative to venous grafts in terms of patency. A tailored, patient-centered approach considering predictors such as diabetes, dialysis dependency, and coronary artery disease along with prediction models may further improve the long-term results in the future.
CRIS-Team Scopus Importer:2022-03-04
Keywords: CLTI; Extra-anatomic bypass reconstruction; Prosthetic bypass grafts; Tibial bypass surgery

The predictive value of microperfusion assessments for the follow-up of tibial bypass grafts - Meyer, Alexander; Yagshyyev, Shatlyk; Lang, Werner; Rother, Ulrich (Journal of Vascular Surgery, 2021)
Objective: We conducted a prospective evaluation of microperfusion parameters after tibial bypass surgery was performed. Differences between grafts with occlusions during follow-up and patent grafts were analyzed in relation to the pedal arch quality. Methods: Patients receiving tibial bypass grafts for chronic limb-threatening ischemia from 2019 to 2020 were included. Assessment of microcirculation (parameters: hemoglobin oxygen saturation [sO2] and flow) was done by laser Doppler flowmetry and white light spectrometry (oxygen-to-see), supine and in elevation, whereas the macrocirculation was evaluated by the ankle-brachial index and duplex ultrasound examination. The quality of run-off was graded for each patient. Measurements were performed preoperatively, 1 day postoperatively, and after 6 months. Patients with graft occlusions during follow-up (OCCLUDED) and patients without occlusions (OPEN) were compared. Results: We included 42 patients (13 women, 29 men; mean age, 76.1 years; range, 60-89 years) were included. The patency of all grafts 1 day after the operation was confirmed by ultrasound examination. The overall analysis of the microcirculation showed significant changes in both the supine and elevated leg position between measurements taken preoperatively, 1 day after the operation, and after 6 months for the parameters sO2 and FLOW (sO2 supine, P = .001; sO2 elevated, P < .001; FLOW supine, P < .001; FLOW elevated, P < .001). The comparison of the values 1 day after the operation yielded significantly decreased microperfusion parameters (both O2 and FLOW) in the group that developed bypass occlusion in the later follow-up period (sO2 supine: OCCLUDED, 35.7% [7.3-65.0] and OPEN, 48.7% [25.0-72.3] P = .011; FLOW supine: OCCLUDED, 27.7 A.U. [12.7-52.7] and OPEN, 57.3 A.U. [16.0-106.7], P = .008). No significant differences in the severity of the arch impairment was found between the OPEN and OCCLUDED groups (P = .651). Absolute values of the parameters sO2 and flow showed no correlation with the pedal arch classification. Conclusions: Significantly poorer microperfusion was detected postoperatively in patients with later occurrence of graft occlusions despite patent grafts on the first postoperative day. Microperfusion measurements might be a possible tool for the prediction of graft failure.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Bypass surgery; Chronic limb-threating ischemia; Graft occlusion; Microperfusion; O2C